Effect of combining aminomethacrylate and fluoride against erosive and abrasive challenges on enamel and dentin - Augusto, Marina Gullo [UNESP]; da Silva, Luis Felipe Oliveira [UNESP]; Lotto, Giovanna [UNESP]; Santos, Tamires Maria de Andrade [UNESP]; Aoki, Idalina Vieira; Torres, Carlos Rocha Gomes [UNESP]; Scaramucci, Tais; Borges, Alessandra Bühler [UNESP] (Wiley, 2024)
This study evaluated the effect of solutions containing aminomethacrylate copolymer (AA) and sodium fluoride (F; 225 ppm F−) or fluoride plus stannous chloride (FSn; 225 ppm F−, 800 ppm Sn2+) against enamel and dentin erosion/abrasion. Solutions F, FSn, AA, F+AA, FSn+AA, and deionized water as negative control were tested. Bovine enamel and dentin specimens (n = 13/solution/substrate) underwent a set of erosion-abrasion cycles (0.3% citric acid [5 min, 4×/day], human saliva [1 h, 4×/day], brushing [15 s, 2×/day], and treatments [2 min, 2×/day]) for each of five days. Initial enamel erosion was evaluated using Knoop microhardness after the first and second acid challenge on day 1, and surface loss with profilometry after day 5. KOH-soluble fluoride was assessed. Data were analyzed with ANOVA/Tukey tests. The combination of fluoride and AA resulted in higher protection against enamel erosion, whereas this was not the case for the combination of AA and FSn. All treatments protected against enamel and dentin loss. The lowest surface loss values were observed with F+AA and FSn+AA. The polymer did not significantly influence the KOH-soluble fluoride formation on enamel/dentin specimens. The aminomethacrylate copolymer effectively enhanced the efficacy of sodium fluoride against initial erosion and improved the control of enamel and dentin wear of F and FSn solutions.
Keywords: dental erosion; dentin; enamel; polymers; sodium fluoride; stannous chloride